Myles textbook for midwives - Cooper, Margaret A.; Fraser, Diane (Elsevier, 2009)
Suitable for midwives, this title provides guidelines, protocols and research evidence, and illustrations. It includes a chapter on emotion work and focuses on normality, whilst equipping midwives to recognise and respond to complexity in childbearing and parenthood